Pengaruh Proyek Zero waste Terintegrasi ESD Terhadap Kompetensi Kolaborasi Dan Self-awareness pada konsep Perubahan Iklim - Damayanti, Teti; Suhendar, Suhendar; Juhanda, Aa (BIOEDUSCIENCE, 2023)
Background: Low collaboration competence and Self-awareness provided to students to face sustainable development because collaboration competence and Self-awareness have not been developed in learning activities, especially to overcome and face global issues in the 21st century. This study aims to apply learning with Project Based Learning to determine the effect on collaboration competence and self-awareness. This model is very rarely used because it requires careful preparation, Methods: The type of research used in this study is quasi-experimental research. The research design in this study used a Non-equivalent Control Group Design. In this design, the determination of the experimental class and control class is not randomly selected. Results: In collaboration and self-awareness competence, the test results obtained a sig value. 2-tailed 0.000 which indicates that there is a significant difference. A correlation test was carried out on Self-awareness competence where the test results between the two obtained a value of 0.596 which was in the medium category. This figure shows that collaboration competencies with Self-awareness competencies have a correlation and show a fairly strong relationship. Conclusion: The implementation of learning by applying an integrated project learning model ESD to the concept of climate change, states that project learning affects collaboration competence and self-awareness with a significance value from the results of the static independent sample T-test 0.000. In addition to these two competencies can be improved through project learning. Collaboration competence and self-awareness competence are positively correlated. With a correlation value of 0.596 belongs to the medium category.